Functional loss of a noncanonical BCOR-PRC1.1 complex accelerates SHH-driven medulloblastoma formation - Kutscher, Lena; Okonechnikov, Konstantin; Batora, Nadja; Clark, Jessica; Silva, Patricia B. G.; Vouri, Mikaella; Rijn, Sjoerd van; Sieber, Laura; Statz, Britta; Gearhart, Micah D.; Shiraishi, Ryo; Mack, Norman; et al. (Genes & development, 2020)
Medulloblastoma is a malignant childhood brain tumor arising from the developing cerebellum. In Sonic Hedgehog (SHH) subgroup medulloblastoma, aberrant activation of SHH signaling causes increased proliferation of granule neuron progenitors (GNPs), and predisposes these cells to tumorigenesis. A second, cooperating genetic hit is often required to push these hyperplastic cells to malignancy and confer mutation-specific characteristics associated with oncogenic signaling. Somatic loss-of-function mutations of the transcriptional corepressor BCOR are recurrent and enriched in SHH medulloblastoma. To investigate BCOR as a putative tumor suppressor, we used a genetically engineered mouse model to delete exons 9/10 of Bcor (BcorΔE9-10) in GNPs during development. This mutation leads to reduced expression of C-terminally truncated BCOR (BCORΔE9-10). While BcorΔE9-10 alone did not promote tumorigenesis or affect GNP differentiation, BcorΔE9-10 combined with loss of the SHH receptor gene Ptch1 resulted in fully penetrant medulloblastomas. In Ptch1+/−;BcorΔE9-10 tumors, the growth factor gene Igf2 was aberrantly up-regulated, and ectopic Igf2 overexpression was sufficient to drive tumorigenesis in Ptch1+/− GNPs. BCOR directly regulates Igf2, likely through the PRC1.1 complex; the repressive histone mark H2AK119Ub is decreased at the Igf2 promoter in Ptch1+/−;BcorΔE9-10 tumors. Overall, our data suggests that BCOR-PRC1.1 disruption leads to Igf2 overexpression, which transforms preneoplastic cells to malignant tumors.